Aksesibilitas Pada Madrasah Ibtidaiyah Swasta Di Kota Banjarmasin - Salmah, Syarifah; Rahmad, Rahmad (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Indonesia is one of the countries that respects the human rights of its citizens. Based on the fundamental constitutional mandate that education is the right of every citizen without exception, one of the indicators is that educational institutions must open opportunities for every citizen. This study aims to evaluate the existing educational facilities in the city of Banjarmasin, precisely some private Islamic Elementary School (MIS). The method in this research is descriptive qualitative. This method aims to describe the situation as a whole and thoroughly related to the selected object. The results of research related to accessibility for people with disabilities still cannot be seen in some of MIS choosen as the object of this study. The results of this study get the fact that all research objects are not friendly to people with dissabilities, such as conventional school steps. Even though the rule of laws is complete, but in fact, the implementation of these laws still encountered some problems until now.Â Accessibility for disability is one indicator as a child-friendly school, so, hopefully this research will be a piece of initial information for stakeholders in the Ministry of Religion in improving the quality of essential Islamic education services.